PERANCANGAN MESIN MOLDING SEBAGAI ALTERNATIF PEMANFAATAN LIMBAH PLASTIK UNTUK BAHAN DASAR SANGKAR BURUNG - Siswanto, Siswanto; Setiawan, Adi Yusuf; Sugiarto, Sugiarto (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Indonesia is a country which has plastic waste problem. Based on BPSâs (1999) data shows that in 1995 volume of import plastic trade in Indonesia especially polipropilena (PP) is 136,122.7 tons whereas in 1999 is 182,523.6 tons. Thus, in that particular time the volume of import plastic trade increases up to 34.15 %. In this case, we create a new innovation in the form of injection molding machine to overcome plastic waste problem. Injection molding machine is a waste processor machine which change plastic waste from solid form into fluidaform then take it into a mold by using screw. Moreover, Injection molding machine could change plastic waste becomes valuable commercial products. One of the products is bird cage. In this case, it helps the bird cage maker to overcome the scarcity of rattan and the explosion volume of plastic waste.Keywords: plastic waste, injection molding machine, product, and bird cage.